Improving students’ speaking skills through the technique “Think Pair Share” in ESP classes - Xulkar Murodjonovna (Genius Journals, 2021)
Article is dedicated to the improving students’ speaking skills through the technique Think-Pair-Share in ESP classes. And in this issue, we investigate that applying a variety of strategies in both academic and social settings by planning, monitoring, and evaluating their learning or by arranging to participate in experiences that will be conductive to language learning who study English. Also, in this work we demonstrate the findings which can improve to work on teaching foreign languages through “Think-Pair-Share” technique in the context-based learning
Keywords: Think-Pair-Share in; speaking; issue; despite